2022
DOI: 10.1097/qad.0000000000003246
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of antibody response to severe acute respiratory syndrome coronavirus 2 mRNA vaccines in people with HIV

Abstract: We identified determinants of SARS-CoV-2 mRNA vaccine antibody response in people with HIV (PWH). Antibody response was higher among PWH less than 60 years, with CD4+ cell count superior to 350 cells/μl and vaccinated with mRNA-1273 by Moderna compared with BNT162b2 by Pfizer-BioNTech. Preinfection with SARS-CoV-2 boosted the antibody response and smokers had an overall lower antibody response. Elderly PWH and those with low CD4+ cell count should be prioritized for booster vaccinations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
(32 reference statements)
4
13
0
Order By: Relevance
“…Some studies reported higher immune responses to both mRNA and adenoviral vector COVID-19 vaccines in PLWH with previous SARS-CoV-2 infection [ 107 , 118 , 120 ] or preexisting cross-reactive T-cell responses correlated with prior exposure to seasonal coronaviruses [ 106 ], suggesting that, similar to what observed in the general population, a preexisting immune memory may boost immune responses to COVID-19 vaccines.…”
Section: Immune Responses To Sars-cov-2 Vaccines In Plwhmentioning
confidence: 98%
See 2 more Smart Citations
“…Some studies reported higher immune responses to both mRNA and adenoviral vector COVID-19 vaccines in PLWH with previous SARS-CoV-2 infection [ 107 , 118 , 120 ] or preexisting cross-reactive T-cell responses correlated with prior exposure to seasonal coronaviruses [ 106 ], suggesting that, similar to what observed in the general population, a preexisting immune memory may boost immune responses to COVID-19 vaccines.…”
Section: Immune Responses To Sars-cov-2 Vaccines In Plwhmentioning
confidence: 98%
“…mRNA vaccines appear to elicit the highest immune responses in this population [ 113 115 , 116 •, 117 ]. Among mRNA vaccines, BNT162b2 has been show less immunogenic than mRNA-1273 [ 100 , 102 ••, 118 ]. However, given the lack of immune thresholds that correlate to protection after vaccination, the clinical significance of such lower immunogenicity is currently unknown.…”
Section: Immune Responses To Sars-cov-2 Vaccines In Plwhmentioning
confidence: 99%
See 1 more Smart Citation
“…In several works, it was suggested that the mRNA1273 may be more immunogenic compared with BNT162b2 vaccine in PLWH [24,25]. In an observational comparative effectiveness study that used administrative claims data in the USA, it was found that among immunocompromised adults, a two-dose mRNA-1273 regimen was more effective in preventing medically attended COVID-19 in any setting (inpatient and outpatient) than 2-dose BNT162b2.…”
Section: Safety and Immunogenicity Of Covid 19 Vaccines In People Liv...mentioning
confidence: 99%
“…To our knowledge, no randomized trials have compared the BNT162b2 and mRNA-1273 vaccines head-to-head. However, there are references to a better performance of mRNA-1273 compared to the BNT162b2 vaccine not only in PLWH ( 18 , 36 ) but also in solid organ transplant recipients ( 37 ) and healthy donors ( 38 , 39 ). Furthermore, the mRNA-1273 vaccine appears to result in significantly lower rates of SARS-CoV-2 infection and related hospitalization ( 40 ).…”
Section: Discussionmentioning
confidence: 99%